The palliative and pernicious effects of racial system justification for the racially privileged and the racially oppressed - Jeannine Alana Bertin; Kemi A. Soyeju; Benjamin A. Saunders (Frontiers in Social Psychology, 2025)
Systemic racism carries disparate and varying impacts for members of advantaged and disadvantaged racial groups, not only materially and socially, but also psychically, with consequences for psychological wellbeing. To further explore the varying psychological experience of advantaged and disadvantaged racial groups within a racialized social system, we apply a system justification perspective by examining the degree to which the acceptance vs. rejection of the racialized status quo is associated with ethnic-racial identity attitudes and, consequently, with psychological wellbeing. Specifically, we hypothesized that for racially advantaged group members, racial system justification would positively predict psychological wellbeing, and decreased ethnic-racial salience and ethnic-racial self-hatred would mediate this relationship. For racially disadvantaged groups, we hypothesized that racial system justification would negatively predict psychological wellbeing mediated by its association with racial self-hatred. However, we also tested a competing hypothesis that racial system justification would positively predict psychological wellbeing for the racially disadvantaged mediated by its association with racial salience – reflecting a possible simultaneously palliative effect of racial system justification among the racially disadvantaged. We tested these hypotheses across two studies examining the relationship between racial system justification, ethnic-racial identity salience and self-hatred attitudes, and psychological wellbeing among White and Black Americans. Among White Americans (Study 1, N = 371), we found that racial system justification predicted wellbeing (i.e., the likelihood of reporting zero – vs. one or more – bad mental health days) and that this association with wellbeing was mediated separately by decreased ethnic-racial self-hatred, and to a lesser extent, ethnic-racial salience. In a sample of Black American participants (Study 2, N = 414), we tested the racial system justification–wellbeing association by examining the association between racial system justification and psychological distress. We found evidence of a positive indirect association between racial system justification and psychological distress through increased racial self-hatred, while also finding some evidence of a negative indirect association between racial system justification and psychological distress through decreased racial salience. The results point to the possibility that while racial system justification is associated with wellbeing for racially advantaged groups, it may have simultaneous palliative and pernicious associations with wellbeing for disadvantaged groups, based on its diverging associations with the salience and self-hatred aspects of racial identity attitudes.